Private Wage Returns to Schooling in Nigeria: 1996-1999 - Adebayo B. Aromolaran (Yale University, Economic Growth Center, 2002)
In the last two decades, primary and secondary school enrollment rates have declined in Nigeria while enrollment rates in post-secondary school have increased. This paper estimates from the General Household Survey for Nigeria the private returns to schooling associated with levels of educational attainment for wage and self-employed workers. The estimates for both men and women are small at primary and secondary levels, 2 to 4 percent, but are substantial at post-secondary education level, 10-15 percent. These schooling return estimates may account for the recent trends in enrollments. Thus, increasing public investment to encourage increased attendance in basic education is not justifiable on grounds of private efficiency, unless investments to increase school quality have higher private returns. With high private returns to post-secondary schooling, students at this level should pay tuition, to recoup more of the public costs of schooling, which may be redistributed to poor families through scholarships.
Keywords: O15; I12; J24; 330; Schooling Investment; Private Wage Returns; Efficiency; Equity; Nigeria; Bildungsertrag; Lohn; Nigeria